2007
DOI: 10.1111/j.1365-2966.2007.12182.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in LP 944−20★

Abstract: We present a new estimate of the lithium abundance in the atmosphere of the brown dwarf LP 944−20. Our analysis is based on a self‐consistent analysis of low‐, intermediate‐ and high‐resolution optical and near‐infrared spectra. We obtain log N(Li) = 3.25 ± 0.25 using fits of our synthetic spectra to the Li i resonance line doublet profiles observed with Very Large Telescope/Ultraviolet–Visual Echelle Spectrograph (VLT/UVES) and Anglo‐Australian Telescope/Segmented Pupil/Image Reformatting Array of Lenslets (A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 81 publications
1
40
0
Order By: Relevance
“…Higher signal-to-noise and resolution spectroscopic observations could be used to study such interesting subpopulations e.g. by searching for the presence of lithium to directly assess age and mass (Pavlenko et al 2007) and the use of higher resolution cross correlation techniques to measure radial velocities and space motions, yielding important kinematic information.…”
Section: Discussionmentioning
confidence: 99%
“…Higher signal-to-noise and resolution spectroscopic observations could be used to study such interesting subpopulations e.g. by searching for the presence of lithium to directly assess age and mass (Pavlenko et al 2007) and the use of higher resolution cross correlation techniques to measure radial velocities and space motions, yielding important kinematic information.…”
Section: Discussionmentioning
confidence: 99%
“…Full spectral energy distribution of SDSS1256 from the optical all the way to the mid-infrared. Overplotted in red is the synthetic spectra from the atmosphere models of Allard et al (2001) generated with the DUST546 code of Pavlenko et al (2007a), which produces a satisfactory fit.…”
Section: Comparison With Theoretical Modelsmentioning
confidence: 99%
“…Our observed absorption is weaker than the two most depleted abundances, suggesting that our tentative detection is . Overplotted in red is the synthetic spectrum from the NextGen atmosphere models of Baraffe et al (1998) generated with the DUST546 code of Pavlenko et al (2007a), which provides the best fit to the data (a low-resolution version is shown for plotting purposes). The synthetic spectra, convolved by the instrument profile, have been generated for a metallicity of [M/H] = −2.0, gravity of log g = 5.0, Li abundance of log N(Li) = −1.0.…”
Section: Comparison With Theoretical Modelsmentioning
confidence: 99%
See 2 more Smart Citations